Analysis of the Impact of Creative Technique on the Motivation of Physical Education Students in Dance Content: Gender Differences. (18th July 2014) - Amado, Diana; Del Villar, Fernando; Sánchez‐Miguel, Pedro Antonio; Leo, Francisco Miguel; García‐Calvo, Tomás
Abstract : The aim of this study was to learn about the effectiveness of two dance teaching techniques, the creative examination technique and the direct instruction technique, on the satisfaction of basic psychological needs, the level of self‐determination, the perception of usefulness, enjoyment and effort of physical education students. Likewise, it purports to analyze the gender difference in the psychological variables addressed in agreement with the teaching technique used, to guide and personalize the treatment of these contents in physical education. A quasi‐experimental design was carried out with four natural groups from two school centers. The direct instruction technique was applied with two groups and the creative examination technique with the other two, in a total of 12 sessions. An initial and final measurement was taken in both groups, and the results revealed the complexity to motivate students after 12 sessions. However, the gender‐dependent analyses offer methodological guidelines, as the creative technique causes adaptative consequences on the male gender and disadaptative consequences on the female gender. By way of conclusion, we can highlight the need to devote more sessions to dance teaching and to apply different treatments depending on the gender.